Association between fasting glucose/high-density lipoprotein cholesterol ratio and cardiovascular disease risk in Chinese middle-aged and older adults: a longitudinal study - Chen, Jintao; Yan, Liying; Chen, Jianhai (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThere is currently no information on the association between the fasting blood glucose/high-density lipoprotein cholesterol ratio (FBG/HDL-C) and cardiovascular disease (CVD) incidence.MethodsParticipants in our study, sourced from the China Health and Retirement Longitudinal Study, were grouped into quartiles by FBG/HDL-C ratio. CVD included self-reported heart disease and stroke. The ability of the FBG/HDL-C ratio to predict CVD was assessed using receiver operating characteristic (ROC) curves. Multivariate Cox regression was used to assess the association of FBG/HDL-C ratios with CVD, and potential nonlinear associations were explored using restricted cubic splines.ResultsDuring the follow-up period from 2012 to 2018, 1,277 out of 6,995 participants (18.26%) developed CVD. There was a nonlinear association between the FBG/HDL-C ratio and CVD incidence in middle-aged and older adults (P for nonlinearity <0.05). Compared to the Q1 of the FBG/HDL-C ratio, the adjusted HRs and 95% CIs for CVD in the Q2 to Q4 were 1.17 (0.98–1.40), 1.41 (1.18–1.68), and 1.56 (1.28–1.90), respectively. ROC curve analysis showed that FBG/HDL-C ratio had the highest diagnostic accuracy for CVD than either FBG or HDL-C alone. Furthermore, incorporating the ratio of FBG/HDL-C into the basic model significantly enhanced the prediction of CVD risk.ConclusionsWe found that FBG to HDL-C ratio was significantly associated with an increased incidence of CVD in middle-aged and older adults. The FBG/HDL-C ratio was shown to be more effective in assessing cardiovascular risk than the use of FBG or HDL-C alone.